2004
DOI: 10.1007/s10143-003-0291-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of melatonin and vitamin E in brain damage due to gamma radiation

Abstract: Gamma radiation is known to cause serious damage in the brain, and many agents have been used for neuroprotection. In this study, lipid peroxidation levels and histopathological changes in brain tissues of whole-body irradiated rats with likely radiation injury were compared to those with melatonin and vitamin E protection. Forty rats in four equal groups were used. The control group received neither radiation nor medication. The remaining groups received doses of 720 cGy in two equal fractions 12 h apart. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…In recent studies radiation necrosis was demonstrated to vary depending on the total radiation dose, frequency, dose per fractions, duration of administration and the size of the exposed area [2,10]. A total dose of 20 Gy may be enough to cause radionecrosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent studies radiation necrosis was demonstrated to vary depending on the total radiation dose, frequency, dose per fractions, duration of administration and the size of the exposed area [2,10]. A total dose of 20 Gy may be enough to cause radionecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A total dose of 20 Gy may be enough to cause radionecrosis. Various clinical studies suggested that higher total doses of radiation are associated with earlier formation of cerebral radionecrosis [1,10]. In addition, it was indicated that, patients who received a higher fractional dose had a significantly higher incidence of radionecrosis than those treated with a higher total dose but a lower fractional dose.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations